Requirement of a complex motor task to identify neuroplastic changes in motor control of the lower extremity in patients with anterior cruciate ligament reconstruction: a fNIRS study - Liu, Ke; Zhu, Qin; Xu, Weidong (Frontiers in Human Neuroscience, 2025)
IntroductionNeuromuscular control is a crucial component in restoring dynamic joint stability following anterior cruciate ligament reconstruction (ACLR). The central nervous system, as the primary control center, is known to exhibit neuroplastic changes. However, motor tasks used to assess brain function in ACLR are often limited to simple and static movements. The current study aimed to compare brain activation between patients with ACLR (ACLR group) and healthy controls (CONT group) during both simple and complex motor tasks and to examine the relationship between brain activity and clinical functions to explore the underlying mechanisms of neuroplasticity.MethodsA total of 35 patients with ACLR and 25 healthy controls participated in this study. Functional near-infrared spectroscopy was used to capture real-time brain activation during knee flexion-extension (K-FE) and single-leg squat (SLS) tasks. Clinical assessments included quadriceps strength, single-leg hop, and self-reported functional outcomes. A two-way mixed-design ANOVA was conducted with one between-subject factor (group) and one within-subject factor (task). The dependent variable was the change in oxyhemoglobin concentration (ΔHbO) across six brain regions.ResultsFor the affected limb tasks, the Primary Somatosensory Cortex (S1) and Supramarginal Gyrus (SMG) showed significant main group effects (PS1 = 0.035, PSMG = 0.002), whereas all brain regions showed significant main effects of task difficulty. A significant interaction between group and task was observed in the SMG (p = 0.036). For the contralateral limb tasks, no significant main effect of group or task was found across all brain regions. Pre-Motor Cortex (PMC), S1, Frontal Eye Fields (FEF), and SMG showed significant interaction effects between group and task (PPMC = 0.013, PS1 = 0.015, PFEF = 0.015, and PSMG = 0.018). Multiple negative correlations were found between increased ΔHbO and functional outcomes in various brain regions, depending on the limb and task.ConclusionBrain activation increased with task difficulty. Patients with ACLR showed lower somatosensory cortex activation during affected limb tasks. Their task adaptation was weaker than that of healthy controls, suggesting deficits in proprioception and a lack of neural resources for adaptation to task complexity. The significant interaction effects observed during the contralateral limb tasks indicated the compensatory role of the contralateral limb. These conclusions were supported by correlations with clinical outcomes.